Insecticidal and Antimicrobial Activity of Triaryl Antimony(V) Derivatives - Yadav, Ram Nath Prasad (Academic Voices: A Multidisciplinary Journal, 2014)
This paper is devoted to the biological activity of the triaryl antimony(V) derivatives which deals with insecticidal and antimicrobial activity of tris(pentafluorophenyl)antimony(V) amides, (Rf)3SbL2 (Rf = C6F5; L = NR2: and triaryl antimony(V) carboxylates, Ar3SbL2 (Ar = C6H5, p-CH3C6H4; L = OCOR. All the compounds were found to exhibit moderate to significant biological activity against P. americana (insect), P. auriginosa, S. Aurens and K. Pneumoniae (bacteria), Synnhemp Rosette (virus), Tobacco Mosaic (Virus) and A. niger, A. flavus and E. moniliforme (Fungus). The compounds with fluoro and amide groups are highly active than that of compounds with phenyl, tolyl and carboxylate groups. Academic Voices, Vol. 3, No. 1, 2013, Pages 40-45 DOI: http://dx.doi.org/10.3126/av.v3i1.9983